1999
DOI: 10.1046/j.1365-2036.1999.00597.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article: liver support systems in acute hepatic failure

Abstract: The treatment of acute hepatic failure has developed rapidly over the last 40 years, reducing morbidity and mortality from this syndrome. Whilst this has been partly attributed to significant improvements in the specialist medical management of these patients, advances in surgical techniques and pharmaceutical developments have led to the establishment of successful liver transplantation programmes, which have improved mortality significantly.This review will examine the clinical impact of alternative methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 107 publications
0
39
0
Order By: Relevance
“…Removal could be accomplished through plasmapheresis, albumin infusions, or albumin dialysis using the molecular adsorbent recirculating system (MARS). 131,132 Perhaps the benefit of bile acid removal already has been shown because patients with type 1 HRS have shown improved survival on MARS treatment. 132 The MARS technique is discussed in greater detail in the sequel article.…”
Section: Other Mechanisms Of Renal Injury In the Setting Of Cirrhosismentioning
confidence: 99%
“…Removal could be accomplished through plasmapheresis, albumin infusions, or albumin dialysis using the molecular adsorbent recirculating system (MARS). 131,132 Perhaps the benefit of bile acid removal already has been shown because patients with type 1 HRS have shown improved survival on MARS treatment. 132 The MARS technique is discussed in greater detail in the sequel article.…”
Section: Other Mechanisms Of Renal Injury In the Setting Of Cirrhosismentioning
confidence: 99%
“…1 Dialysis as a biocompatible method failed to remove the majority of toxins accumulating in liver failure because of their high protein-binding rate that prevented their passage through protein-impermeable dialysis membranes. More invasive detoxification methods, such as hemo-or plasmasorption, enabled greater clearance of protein-bound toxins because of direct contact between the sorbent and albumin-toxin complex and the large surface of these sorbents.…”
mentioning
confidence: 99%
“…2 However, negative side effects arising from plasma-sorbent contact representing an unsatisfying biocompatibility outweighed the basically positive effects of this treatment. 1,3 Another method is the removal of the patient's plasma by centrifugation or filter devices and replacement with fresh frozen plasma. 4 This method limits the amount of the removed toxins to that contained in the convection-filtered plasma in contrast to adsorption methods based on diffusive removal of toxins.…”
mentioning
confidence: 99%
“…Major side-effects are hypernatraemia, metabolic alkalosis and a decrease in colloid osmotic pressure. 16,17 There are no randomized trials on plasma exchange and case series reported no improvement in neurological function or mortality, despite improved coagulation parameters and decreased cytokine and endotoxin load. 86,87 High-volume plasmapheresis (HVP) is a more extreme method of plasma exchange and consists of exchanging more than 10 L of plasma.…”
Section: Plasmapheresis (Plasma Exchange)mentioning
confidence: 99%
“…[16][17][18][19] More specifically, biological devices include approaches with either whole organ perfusion using animal or human livers or with support systems that are based on a hepatocyte bioreactor. These techniques endeavour to replace the whole of hepatic functions.…”
Section: Which Types Of Liver Support Are Available?mentioning
confidence: 99%